Erythrocytes and Blood Coagulation - Surgenor, Douglas MacN. (Thrombosis and Haemostasis, 1974)
The action of intact and hemolyzed red cells in in vitro clotting systems is analyzed against the background of the clinical manifestations of red cell procoagulants in incompatible transfusions and hemolytic anemias in man and in experimental animals. It is suggested that the nature of the lesion in the stroma may be of importance in determining the biological effects.